Genomic analysis of KEL*03 and KEL*04 alleles among Thai blood donors - Oytip Nathalang; Panasya Rassuree; Kamphon Intharanut; Wanlapa Chaibangyang; Núria Nogués (AOSIS, 2024)
Background: The Kell blood group system is clinically important in transfusion medicine, particularly in patients with antibodies specific to Kell antigens. To date, genetic variations of the Kell metallo-endopeptidase (KEL) gene among Thai populations remain unknown. Objective: This study aimed to determine the frequencies of KEL*03 and KEL*04 alleles among Thai blood donors using an in-house polymerase chain reaction-sequence-specific primer (PCR-SSP) method. Methods: Blood samples obtained from 805 unrelated central Thai blood donors at a blood bank in Pathumthani, Thailand, from March 2023 to June 2023, were typed for Kpa and Kpb antigens using the column agglutination test, and the results for 400 samples were confirmed using DNA sequencing. A PCR-SSP method was developed to detect the KEL*03 and KEL*04 alleles, and genotyping results were validated using known DNA controls. DNA samples obtained from Thai donors in central (n = 2529), northern (n = 300), and southern (n = 427) Thailand were also genotyped using PCR-SSP for comparison. Results: All 805 (100%) donors had the Kp(a−b+) phenotype. The PCR-SSP genotyping results agreed with the column agglutination test and DNA sequencing. All 3256 Thai blood donors had the homozygous KEL*04/KEL*04 genotype. Frequencies of the KEL*03 and KEL*04 alleles among Thai donors differed significantly from those of Japanese, Native American, South African, Brazilian, Swiss, and German populations. Conclusion: This study found a 100% KEL*04 allele frequency in three Thai populations. These data could provide information on KEL*03 and KEL*04 allele frequencies to estimate the risk of alloimmunisation in Thai populations. What this study adds: This study demonstrates that in-house PCR-SSP can be used to determine KEL*03 and KEL*04 alleles to predict Kpa and Kpb antigens. Even though only homozygous KEL*04/KEL*04 genotypes were found among Thai donor populations, the established PCR-SSP method may be useful for estimating the risk of alloimmunisation in other populations.